PENGARUH LIPUTAN MEDIA, KEPEKAAN INDUSTRI, DAN STRUKTUR TATA KELOLA PERUSAHAAN TERHADAP KUALITAS PENGUNGKAPAN LINGKUNGAN - Solikhah, Badingatus; Winarsih, Arga Mustika (UI Scholars Hub, 2016)
This study aims to examine the influence of media coverage, industry sensitivity and corporate governance structure on the quality of environmental disclosure. The sample of this study is taken from six industries (mining, energy, chemicals, pharmaceuticals, cosmetics, food and beverages) from Indonesia Stock Exchange during 2011, 2012 and 2013. This study uses panel data regression analysis and employs 128 listed companies as the samples of the study. The results show that industry sensitivity, multiple directorship, board size, firm size and ROA positively affect the quality of environmental disclosure. The results also show a negative effect of independent commissionaire on environmental disclosure. This study also provides evidence that media, gender and institutional ownership have no effect on environmental disclosure.